Sejarah Nalar Diplomasi Politik Indonesia di Kawasan Timur Tengah - Imam Nawawi (Institut Agama Islam Negeri (IAIN) Salatiga, 2018)
The historiography of Indonesian political diplomacy in the Middle-East regions faces obstacles from the researchers themselves. The perspective contradictions are compounded by sorting data and sources. The appearance of Indonesian political diplomacy in the Middle East regions according to the Middle East researchers and academics themselves seems to be gloomy and lethargic, because they demand more than what Indonesia has achieved and done. Indonesia is considered not too interested in contributing to the recovery of conflict countries and the acceleration of the transition to democratic values. According to the other researchers who are not based on the Middle East institutions, the appearance of Indonesian political diplomacy in the Middle East is quite positive and slightly vague. Unlike the case with the version that came out directly from the Government of the Republic of Indonesia about their achievements and performance in building diplomatic relations with related countries in the Middle East. Some achievements are recorded annually and submitted to the public in their annual reports. The constraints in historical writing can be overcome by the historical reasoning approach which tries to examine reason, thought and awareness, and which not only focuses on historical facts and events themselves. This approach is able to map the narrative contestation and discourse ideology, and find solutions to the problems.